EFEKTIVITAS PENGGUNAAN BAHASA INGGRIS DALAM PENAMAAN MENU KULINER DI MISSBEE PROVIDORE RESTAURANT - Zia Kemala; Khoirul Fajri (Bogor Hospitality Journal, 2024)
entrepreneurs must be able to facilitate the language of their target consumers. The research was carried out at Miss Bee Providore, which has received the Travelers' Choice Award from Trip Advisor with the highest number of reviews. The method used in this research is qualitative descriptive. Data collection techniques included questionnaires, interviews, and documentation studies. This research involved key informants such as visitors, the owner of Miss Bee Providore Restaurant, representatives from PHRI, AKAR, culinary tourism industry experts, as well as academics and associations related to language and culinary tourism. Based on the research findings, two main points were identified. Firstly, there are five criteria for naming products using a foreign language, namely it should be easy to pronounce, easy to understand, relevant to the product, have a positive image, and be unique. Secondly, the effectiveness of using English in product naming aims to create a product image, enhance product quality, create uniqueness, assist in information compilation, create differentiation, generate purchase desire, create positive attitudes/feelings, and establish a basis for expansion.